(3TQM Gdabg GdCcHQs - (3GdeZfjSGhj, CHh GdefJgi, TgGH GdOjf, CMeO Hf eMeO, J (B1000 (3g`s
(3ChdgG (B:s
(3GdMeO ddg GdPj gOGfG Edi WQjb GdSfI hGdLeGYI (B... (3Ef cJGH Gdabg GdCcHQ GdPj Ufag GdEeGe GdCYXe cJGH UMjM ebHhd bGd GdTjN GdEeGe aNQ GdESdGe Ydj GdjROhj j CUhd Gdabg GdYGe (B...s
(3BNQgG (B:s
... (3hdG fQVi HGdMcejf CHG ehSi GdCTYQj hYeQh Hf GdYGU heOGQ cdGe GdQGaVjI Ydi dYf CHj HcQ hYeQ QVj Gddg YfgeG hJcajQgeG hjJHQDhf efgeG heOGQ cdGe GdbOQjI Ydi faj GdbVGA hGdbOQ JeJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B1\234s
(3cTa GdXfhf (B2\1287s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds